Simultaneous LC–MS/MS determination of 40 legal and illegal psychoactive drugs in breast and bovine milk. (15th April 2018) - López-García, Ester; Mastroianni, Nicola; Postigo, Cristina; Valcárcel, Yolanda; González-Alonso, Silvia; Barceló, Damia; López de Alda, Miren
Highlights: A LC–MS/MS method was developed to determine 40 psychoactive drugs in milk. The method allows the investigation of 10 drugs for the first time in milk. Method was validated in breast milk and four different classes of bovine milk. Caffeine was the only compound found to be present in the milk samples analysed. Abstract: This work presents a fast, sensitive and reliable multi-residue methodology based on fat and protein precipitation and liquid chromatography-tandem mass spectrometry for the determination of common legal and illegal psychoactive drugs, and major metabolites, in breast milk. One-fourth of the 40 target analytes is investigated for the first time in this biological matrix. The method was validated in breast milk and also in various types of bovine milk, as tranquilizers are occasionally administered to food-producing animals. Absolute recoveries were satisfactory for 75% of the target analytes. The use of isotopically labeled compounds assisted in correcting analyte losses due to ionization suppression matrix effects (higher in whole milk than in the other investigated milk matrices) and ensured the reliability of the results. Average method limits of quantification ranged between 0.4 and 6.8 ng/mL. Application of the developed method showed the presence of caffeine in breast milk samples (12–179 ng/mL).